Ảnh hưởng của nhận thức lợi ích đến thái độ và hành vi của cộng đồng địa phươngtham gia chương trình phát triển du lịch bền vững tại khu vực duyên hải Nam Trung Bộ - Lê Chí Công; Hồ Huy Tựu (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
This study is conducted based on integrating three theories: sustainable tourism development, social exchange, and behavior. A quota survey sample is collected from the local community with 444/500 participants in Khanh Hoa, Binh Dinh, and Quang Nam provinces. The results show that all the six hypotheses are supported. Specifically, the attitude of the local community toward the sustainable tourism development program plays a mediator role in the relationship between the perception of benefits and the behavioral intentions of the community participating in the tourism development program. On the basis of the research findings, several policies are accordingly suggested, enabling the tourism industry to promote the role of local communities in the sustainable development of beach tourism in the South Central Coast.
Keywords: Benefit; Attitude; Behavior; Intention; Community; Tourism